Unbalanced sediment transport by tidal power generation in Lake Sihwa. (July 2021) - Kim, J.W.; Ha, H.K.; Woo, S.-B.; Kim, M.-S.; Kwon, H.-K.
Abstract: An in-situ observational study was conducted to understand the sediment transport processes disturbed by the flood generation type of Sihwa tidal power plant (TPP). A surface mooring was deployed in Lake Sihwa (inside of TPP) to collect time-series data of the current velocity and suspended sediment concentration (SSC). A TPP with a capacity of 254 MW has four sequential phases (power generation–standby–drain–standby) of operation. The SSC during power generation was one order of magnitude higher than that during drain, which led to heavily unbalanced sediment fluxes. The total residual sediment flux was always negative (into the lake), which was attributed to the mean advection processes associated with the discharge. Over 18 day mooring period, 78.28 tons m −1 of sediment was delivered to the lake. The source of delivered sediment might be attributed to more local resuspension than the sediment inflow through the gates of TPP. Since the maximum sediment influx during power generation occurred within the water head difference of 4–6 m, the reduction in discharge rate can be a possible measure for solving the sediment accumulation within Lake Sihwa. Highlights: The operation of tidal power plant induced the unbalanced sediment flux. The maximum sediment influx occurred within the water head difference of 4–6 m. Sediment budget into the lake tends to increase due to the advective effect.